Lennox‐Gastaut syndrome with late‐onset and prominent reflex seizures in trisomy 21 patients - Ferlazzo, Edoardo; Adjien, Constant K.; Guerrini, Renzo; Calarese, Tiziana; Crespel, Arielle; Elia, Maurizio; Striano, Pasquale; Gelisse, Philippe; Bramanti, Placido; Di Bella, Paolo; Genton, Pierre (Epilepsia (Copenhagen), 2009)
Summary Purpose:  Lennox‐Gastaut syndrome (LGS) is a severe epileptic condition characterized by multiple seizure types including tonic seizures, slow spike‐and‐wave discharges on electroencephalography (EEG), and cognitive impairment. LGS can occur in apparently healthy subjects or in patients with preexisting brain damage. The onset peaks between 3 and 5 years of age and the prognosis is usually poor. Herein we report 13 subjects with trisomy 21 who developed LGS. Methods:  We retrospectively reviewed the clinical and EEG data of consecutive patients with LGS and trisomy 21 referred to five epilepsy centers over the last 30 years. Results:  Data for 13 patients (8 male, 5 female) were collected. The mean age at onset was 9.1 years (range 5–16). The mean age at last follow‐up was 23.5 years (range 11–43 years). Seizure onset was after age 8 years in eight (62%) patients and between age 5 and 8 in the other five. In none of the cases did a West syndrome precede the onset of LGS. Nine of 13 patients (69%) had unambiguous reflex seizures, mostly precipitated by sudden unexpected sensory stimulations, usually preceding or accompanying the onset of a full‐blown LGS picture. Interictal and ictal EEG findings were typical for LGS. All patients were drug‐resistant. Discussion:  Patients with trisomy 21 may present a peculiar LGS, characterized by late onset and high occurrence of reflex seizures. Mechanisms underlying this particular presentation of LGS may include dendritic rarefaction and decreased interneurons, as well as functional abnormalities leading to overall decreased brain inhibition in these patients.